CREATIVE TEACHING - Ghofur, Abd. (OKARA: Jurnal Bahasa dan Sastra, 2017)
The objective of this writing is asking English teachers to make a creative teaching, to endeavor increasing their quality in teaching learning process. In these cas the classroom teacher can choose the methods and materials according to the needs of the learners, the preferences teacher, and the constrainst of the school or educational setting and the methods is considered in terms of its links to more general linguistics, psychological, or educational traditions. Finally it will enable teachers to become better informed about the nature, strengths, and weaknesses of methods and approaches so they can better arrive at their own judgement and decisions.